Peran Kelembagaan Pertanian dalam Pengembangan Usaha Tani Biofarmaka (Studi Kasus di Desa Trosono, Kecamatan Parang, Kabupaten Magetan) - Yudi Setiawan; Eny Lestari; Suwarto Suwarto (Universitas Sebelas Maret, 2024)
Biopharmaceuticals are a type of plant that can be used as medicine. Developing farming for a commodity requires the role of various parties, one of which is agricultural institutions. Agricultural institutions are an important element in agricultural modernization and supporting farming in Trosono Village, which is known as a producer of biopharmaceutical commodities, especially ginger and turmeric. This research aims to determine the system, the role of institutions, and the impact of institutional roles on agriculture in the development of biopharmaceutical farming in Trosono Village. The research used a qualitative descriptive method and the determination of informants was carried out purposively and snowballing with a total of 13 informants consisting of administrators of agribusiness microfinance institutions, farmer group administrators, extension workers, middlemen, farmers and village heads. Data analysis used Miles and Huberman’s interactive analysis, then data validity was carried out using source triangulation and method triangulation techniques. The results of the research show that Trosono Village has an institutional system for both agricultural input and output, namely the Agribusiness Microfinance Institution, the Association of Farmer Groups, the Agricultural Extension Center and middlemen who work with each other in relation to biopharmaceutical farming. Each institution has a role that is demonstrated in the activities of each institution. However, in terms of institutional conditions in Trosono Village, it is still not optimal in accordance with the existing ideal conditions. The role of institutional activities in developing farming has a social impact on farmers such as improving relations, harmony and economic impacts in the form of easy access to capital, subsidies and marketing, so there has been no improvement in economic conditions. Coordination and assistance between agricultural institutions for biopharmaceutical commodities is needed so that a synergy arises in the implementation of programs and activities in the context of increasing biopharmaceutical commodities.